Exploring Online Health Information Seeking Behaviour (OHISB) among young adults: A scoping review protocol - Kristine Moksnes Bratland; Charlotte Wien; Torkjel M Sandanger (BMJ Open, 2024)
Introduction In recent years, information technology and social media have experienced unprecedented growth, particularly in the Nordic countries. However, there is a noticeable lack of comprehensive understanding regarding the latest research findings on online health information seeking behaviour (OHISB) among young adults (18 to >30). There is a need to conduct an updated review to identify knowledge gaps in where young adults find health information and their user interface preferences and to provide research-based guidance and recommendations to governments, health organisations and social media platforms on how to facilitate this prominent pattern. The scoping review protocol outlines a study that will systematically map the existing literature on young adults’ preferences for digital platforms and platform characteristics in relation to OHISB, enabling the identification of promising areas for further research and the development of more effective interventions to promote healthy and informed choices. Conducting a scoping review is imperative to gain a comprehensive understanding of young adults’ OHISB and support the next generation of dissemination that promotes accurate and reliable digital health information.Methods and analysis The scoping review will use Arksey and O’Malley’s methodological framework (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR)) and employ the citation pearl method and the Sample, Phenomenon of Interest, Design, Evaluation, Research type model to design the search strategy. To identify relevant literature, three databases will undergo a search: Scopus, Web of Science and EMBASE. Additionally, a subsidiarily grey literature search will be conducted in Google Scholar. The data charting process will conform to the PRISMA-ScR standard and will be further structured with EndNote. Qualitative and quantitative analyses of the extracted data will be developed using EndNote and Excel.Ethics and dissemination Conducting a scoping review involves secondary data analysis of publicly available sources and does not require an ethical review. The protocol will be published to ensure transparency. The scoping review results will be disseminated through open-access peer-reviewed publications, national and international conferences, social media platforms, newspapers and YouTube to service users and stakeholders.